INVENTARISASI DAN PEMANFAATAN JENIS-JENIS MANGROVE OLEH MASYARAKAT DI KAMPUNG AUKI DAN YERI, KEPULAUAN PADAIDO, KABUPATEN BIAK NUMFOR, PROVINSI PAPUA - Ester Novita Togatorop; Fanny F.C. Simatauw; Sampari S. Suruan; Frits N.Y. Rumbino (Yayasan Nusantara Hasana Berdikari, 2023)
Overall, data information regarding the types of mangroves and their utilization patterns by communities in the Padaido Islands Conservation Area is not yet known with certainty and requires additional specific information, so this research was conducted to determine the condition and distribution of mangroves as well as mangrove utilization patterns by communities in the Padaido Islands, especially in Auki and Yeri village. This research was conducted from 03 July to 04 August 2023, where each type of mangrove at the research location was identified and the number of individuals per type was counted using a transect line data collection technique using a combination of observation plot lines (observation quadrants), while the pattern data The use of mangroves was taken using an interview approach to people who use mangroves. Data on the composition of the type and number of individual mangroves were analyzed descriptive quantitative using the mangrove ecological index formula, while data on mangrove utilization was analyzed descriptive qualitative. Based on the results of the analysis, it was found that in K. Auki (Padaidori District), the composition of mangrove species was dominated by species from the genus Bruguiera sp., with a total number of mangroves of 34 individuals, while in K. Yeri (Aimando District), the composition of mangrove species was dominated by Soneratia sp, Rhizopora sp, and Lumnitzera sp., with a total of 30 mangrove individuals. The highest relative density and density value for mangroves is in K. Auki, namely 0.032 Ind/m2 (320 individuals per hectare) and a relative density of 47.06% (Bruguiera gymnorrhiza type), while in K. Yeri the highest density and relative density value is 0.02 Ind. /m2 (200 individuals per hectare) and a relative density of 33.33% (Rhizophora mucronata and Lumnitzera littores types). The mangrove diversity index value ranges from 1,129 (K. Auki) to 1,397 (K. Yeri) and the mangrove dominance index value at the two research locations, was K. Auki is 0.358 and K. Yeri is 0.273. The mangroves used by the community are of the types bruguiera gymnorrhiza, rhizophora mucronata, pandanus spp, and sonneratia alba.